COLLEGE OF ART AND DESIGN (International Library of African Music, 1970)
A new "College of Art and Design”, part of a national plan for developing technological self- sufficiency, is planned to open as part of the Evelyn Hone College in Lusaka, Zambia, in March, 1970.
Keywords: African Music